IDIOMS IN THE LIGHT OF LINGUOCULTUROLOGY (Scientific journal of the Fergana State University, 2026)
The article considers phraseological units as an important element of the language system, possessing stable semantics and a specific structure, and analyses the semantic features of phraseological units, their metaphorical nature, cultural conditioning, and structural types. In addition, key features of idiomatic expressions are identified, and their role in reflecting the national mentality and linguistic picture is emphasised.